MENGUKUR DAYA SAING OUTPUT DI PASARAN INTERNASIONAL : KOMODITI TUNGGAL ATAU OUTPUT INDUSTRI SEJENIS - MUHAMMAD TEGUH (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
Many people feel confused when they try to seek an appropriate technique to solve phenomenons in th real world. We face many tools existed arround us, some of them can be used for the same purpose, but unlike for others. People could not put unappropriate techniques to solve the same problems they face. This paper try to give you some explanations how to choose an appropriate technique dealing with market competition, especially for a single commodity, or an industry.Â  I suggest you, you can compute a competitionâ€™s index among competitors in the market for a single commodity or an industry using IPij. By using this method, I hope you will get a better comparative advantage indicator from time to time.